Linguistic Word Taboos in Chinese Culture - Andrew, Yau-hau Tse (2011)
Taboo is the prohibition of an act or the use of a word under pain of punishment. This paper is a combination of socio-psychological and linguistic study since homophonic word taboo is a socio-linguistic phenomenon in Chinese culture. The objective of this piece of research is to investigate Chinese attitudes towards homophonic word taboos in Hong Kong. Questionnaires were distributed to seven groups of people, old and young, male and female, with questions related to number four, which is phonologically linked to the meaning of ‘death’ in Chinese culture. The findings revealed that old females were more superstitious than young students; no significant difference was found between old males and old females; young male students and young female students were comparatively not superstitious. To conclude, superstition is a social phenomenon and further research is needed to investigate the impacts of word taboos in different cultures. Keywords: word taboos, culture, sociolinguistics, psycholinguistics, superstition